Microdosimetric measurements of a clinical proton beam with micrometer‐sized solid‐state detector. Issue 11 (13th October 2017) - Anderson, Sarah E.; Furutani, Keith M.; Tran, Linh T.; Chartier, Lachlan; Petasecca, Marco; Lerch, Michael; Prokopovich, Dale A.; Reinhard, Mark; Perevertaylo, Vladimir L.; Rosenfeld, Anatoly B.; Herman, Michael G.; Beltran, Chris
Abstract : Purpose: Microdosimetry is a vital tool for assessing the microscopic patterns of energy deposition by radiation, which ultimately govern biological effect. Solid‐state, silicon‐on‐insulator microdosimeters offer an approach for making microdosimetric measurements with high spatial resolution (on the order of tens of micrometers). These high‐resolution, solid‐state microdosimeters may therefore play a useful role in characterizing proton radiotherapy fields, particularly for making highly resolved measurements within the Bragg peak region. In this work, we obtain microdosimetric measurements with a solid‐state microdosimeter (MicroPlus probe) in a clinical, spot‐scanning proton beam of small spot size. Methods: The MicroPlus probe had a 3D single sensitive volume on top of silicon oxide. The sensitive volume had an active cross‐sectional area of 250 μm × 10 μm and thickness of 10 μm. The proton facility was a synchrotron‐based, spot‐scanning system with small spot size ( σ  ≈ 2 mm). We performed measurements with the clinical beam current (≈1 nA) and had no detected pulse pile‐up. Measurements were made in a water‐equivalent phantom in water‐equivalent depth (WED) increments of 0.25 mm or 1.0 mm along pristine Bragg peaks of energies 71.3 MeV and 159.9 MeV, respectively. For each depth, we measured lineal energy distributions and then calculated the dose‐weighted mean lineal energy, y ¯ D . The measurements were repeated for two field sizes: 4 × 4 cm 2 and 20 × 20 cm 2 . Results: For both 71.3 MeV and 159.9 MeV and for both field sizes, y ¯ D increased with depth toward the distal edge of the Bragg peak, a result consistent with Monte Carlo calculations and measurements performed elsewhere. For the 71.3 MeV, 4 × 4 cm 2 beam (range at 80% distal falloff, R80  = 3.99 cm), we measured y ¯ D = 1.96 ± 0.08  keV/μm at WED = 2 cm, and y ¯ D = 10.6 ± 0.32  keV/μm at WED = 3.95 cm. For the 71.3 MeV, 20 × 20 cm 2 beam, we measured y ¯ D = 2.46 ± 0.12  keV/μm at WED = 2.6 cm, and y ¯ D = 11.0 ± 0.24 keV/μm at WED = 3 cm. For the 159.9 MeV, 4 × 4 cm 2 beam (R80  = 17.7 cm), y ¯ D = 2.24 ± 0.15  keV/μm at WED = 5 cm, and y ¯ D = 8.99 ± 0.71  keV/μm at WED = 17.6 cm. For the 159.9 MeV, 20 × 20 cm 2 beam, y ¯ D = 2.56 ± 0.10  keV/μm at WED = 5 cm, and y ¯ D = 9.24 ± 0.73  keV/μm at WED = 17.6 cm. Conclusions: We performed microdosimetric measurements with a novel solid‐state, silicon‐on‐insulator microdosimeter in a clinical spot‐scanning proton beam of small spot size and unmodified beam current. For all of the proton field sizes and energies considered, the measurements of y ¯ D were in agreement with expected trends. Furthermore, we obtained measurements with a spatial resolution of 10 μm in the beam direction. This spatial resolution greatly exceeded that possible with a conventional gaseous tissue‐equivalent proportional counter and allowed us to perform a high‐resolution investigation within the Bragg peak region. The MicroPlus probe is therefore suitable for applications in proton radiotherapy.